DASAR KEWENANGAN PEMERINTAH DAERAH KABUPATEN BADUNG DALAM MEMBERIKAN STANDAR PELAYANAN BAGI PEREMPUAN DAN ANAK KORBAN KEKERASAN - Anak Agung Istri Ari Atu Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Base on Article 28 G paragraph (1) The Constitution of the Republic of Indonesia to declare,that every person has the right to protection of self, family, material, dignity, and propertyunder his control, and has the right to feel secure and protection from threats to do ornot to do that is a human right. In addition, under Article 20 of act Child Protection toregulate that the State, government, society, family, and the parents are obliged responsiblefor the implementation of child protection. In article 5 of act on the Elimination of DomesticViolence to declare that every person is prohibited from domestic violence against people inthe scope of the household by means of: physical violence; psychological violence; sexualviolence; or neglect of household.Based on the reality that exsistence of women and children are the group who are becomingvictims of violence. Many factors contribute to the violence against women and children,among which is a factor of a patriarchal culture that is still views women is lower than inmen. Another thing is also very influence violence as a false perception of violence whichconsiders that violence as a matter of course, and the rights of the offender.The purpose of research is to determine the authority of local government in providingprotection for women and children victims of violence. So, want to know the forms andmechanisms of a given service standards Badung regency administration especially to womenand children victims of violence. Specific targets to be achieved is to provide information tothe public that is legally local governments have the authority to provide service standardsand to determine also whether local governments already have a minimum service standardsand other forms of care is given to women and children victims of violence , given the manywomen and children victims of violence have not got a good service or minimum service asa form of protection for women and children victims of violence. The method is normativeresearch.Base on discussion can be presented , the first, that authority Badung Government in providingservice standards for women and children victims of violence. That service standards hasbeen regulated in act Number. 15 of 2013, that is the title of act the Protection of Womenand Children Victims of Violence. Second, that the standard services forms of BadungGovernment have five (5) types of shapes minimum service standards.